A method for preparing a nanoparticle-rich composite material

CN122879010APending Publication Date: 2026-10-09NATIONAL INNOVATION MATERIALS TECHNOLOGY (SHENYANG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611023413.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]为解决上述问题,现有技术中已开发多种润滑剂产品,但仍存在显著缺陷:一方面,传统润滑剂多依赖单一成分的润滑作用,抗磨减摩效果有限,难以实现摩擦形式的根本性改善,无法满足高温、重载、腐蚀性等复杂工况下的使用需求;另一方面,部分改性润滑剂通过添加颗粒增强相提升性能,但存在颗粒粒径控制不精准、易团聚,导致无法适配工作表面微小间隙(50-200nm)的问题,甚至可能因颗粒尺寸超限改变核心零件关键尺寸数据,影响设备安全稳定运行;此外,现有含纳米颗粒的润滑剂还存在应用场景受限、分散均匀性差、储存与使用稳定性不足等弊端,难以兼顾润滑效果、适配性与设备安全性;

Benefits of technology

1.实现摩擦形式颠覆性转变,显著降低摩擦损失:本发明通过严格的粒度级配筛选与适配性设计,确保复合粉料颗粒可精准植入工作表面的微小间隙,在摩擦界面形成类轴承的结构,将传统滑动摩擦转变为滚动摩擦,从根本上降低摩擦系数与磨损量,有效减少能源消耗,助力提升能源利用率,契合绿色低碳发展需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879010A_ABST
    Figure CN122879010A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lubricant preparation, and particularly discloses a preparation method of a nano-particle-rich composite material, which takes a lubricant as a carrier, disperses composite powder containing synthetic nano-particles, nano-scale graphite particles, nano-scale chrysotile particles and nano-scale anthophyllite particles in the lubricant, and prepares the lubricant which can be implanted into the tiny gap of two or more working surfaces in mutual sliding friction and produce a bearing-like effect, so that the sliding friction is changed into rolling friction. Through strict particle size grading screening and adaptability design, the composite powder particles can be precisely implanted into the tiny gap of the working surface, a bearing-like structure is formed at the friction interface, the traditional sliding friction is changed into rolling friction, the friction coefficient and the wear amount are fundamentally reduced, the energy consumption is effectively reduced, the energy utilization rate is improved, and the green and low-carbon development demand is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lubricant preparation technology, specifically to a method for preparing a composite material rich in nanoparticles. Background Technology

[0002] In industrial production, mechanical equipment operation and other fields, friction and wear are one of the core problems leading to energy waste and component failure.

[0003] To address the aforementioned issues, various lubricant products have been developed in the existing technology, but significant drawbacks remain: On the one hand, traditional lubricants often rely on the lubricating effect of a single component, resulting in limited anti-wear and friction-reducing effects, making it difficult to fundamentally improve the friction profile and meet the needs of complex working conditions such as high temperature, heavy load, and corrosiveness; on the other hand, some modified lubricants improve performance by adding particulate reinforcing phases, but suffer from inaccurate particle size control and easy agglomeration, leading to an inability to adapt to the tiny gaps (50-200nm) on the working surface, and even potentially altering the critical dimensional data of core components due to excessive particle size, affecting the safe and stable operation of equipment; furthermore, existing lubricants containing nanoparticles also have drawbacks such as limited application scenarios, poor dispersion uniformity, and insufficient storage and use stability, making it difficult to balance lubrication effect, compatibility, and equipment safety. Based on the need for the cross-integration of tribology, nanotechnology and materials science, the development of a new type of lubricant that can precisely adapt to tiny gaps, achieve a revolutionary change in friction patterns and be suitable for various working conditions has become a key technological direction for solving friction and wear problems, improving energy efficiency and promoting green and low-carbon development. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a method for preparing nanoparticle-rich composite materials, thus solving the problems mentioned in the background section.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a composite material rich in nanoparticles, using a lubricant as a carrier, dispersing a composite powder containing synthetic nanoparticles, nano-sized graphite particles, nano-sized chrysotile asbestos particles, and nano-sized white stone particles in the lubricant. The resulting lubricant can be embedded in the micro-gap between two or more mutually sliding and rubbing working surfaces and generate a bearing-like effect, realizing the transformation of sliding friction into rolling friction. The method includes the following steps: Step 1, Particle size distribution screening: Based on the friction application scenario of the target machinery, synthetic nanoparticles, nano-scale graphite particles, nano-scale chrysotile asbestos particles and nano-scale white stone particles are screened to remove particles with excessive particle size and ensure that the particles are suitable for the tiny gaps on the working surface. Step 2, Surface cleaning and purification: The screened synthetic nanoparticles are surface cleaned and dispersed and then dried. The screened nanoscale graphite particles are then purified at high temperature. Step 3, Composite Powder Preparation and Ultrasonic Treatment: The synthetic nanoparticles and nano-scale graphite particles after surface cleaning and purification are mixed with the screened nano-scale chrysotile asbestos particles and nano-scale white stone particles in a preset mass ratio to obtain composite powder. The composite powder is then subjected to ultrasonic surface suspension energy treatment. Step 4, Blending and Finished Product Preparation: The ultrasonically treated composite powder and lubricant are blended and stirred in stages. After adding auxiliary materials, stirring is continued. After the temperature of the mixed system drops to the preset temperature, it is packaged to obtain a lubricant rich in nanoparticles.

[0006] Preferably, the particle size distribution screening in step 1 is based on the particle size distribution span coefficient. The core criterion is particle size distribution screening, and the specific operational procedures include the following: S11: Particle Sample Collection and Particle Size Distribution Detection; At least three parallel samples were drawn from each of the synthetic nanoparticles, nano-scale graphite particles, nano-scale chrysotile asbestos particles, and nano-scale white stone particles to be screened. Each sample weighed 5-10g. The particle size distribution data of each sample was determined using a laser particle size analyzer. , , value; S12: Span coefficient calculation and compliance determination; based on each sample , , The span coefficient is calculated using the following formula. : ; in, The particle size value when the cumulative particle size distribution reaches 10%, in nm; The median particle size when the cumulative particle size distribution reaches 50%, in nm; This refers to the particle size value when the cumulative particle size distribution reaches 90%, in nm; if the span coefficient S of three parallel samples of a certain type of particle is ≤0.7, and All are in the 20-80nm range. If all particles are ≤120nm, the particle size is considered acceptable; otherwise, they need to be screened again. S13: Removal and re-inspection of out-of-limit particles; For qualified particles, use a diameter-limiting filter for batch screening to remove out-of-limit particles; After screening, randomly select 3 parallel samples of the screened particles and repeat steps S21-S12 for re-inspection to ensure that the re-inspection pass rate is ≥99.5% and that the particles can be implanted into the micro gaps of the working surface of 50-200nm.

[0007] Preferably, in step 1, a diameter-limiting filter is used to remove particles exceeding the size limit, and the filter pore size setting includes the following process: S21: Pore size calculation; calculate the pore size of qualified particles. The maximum value is calculated using the following formula to determine the theoretical pore size of the filter. :

[0008] in, The safety filtering coefficient has a value range of 0.12-0.18. S22: Filter selection and pore size calibration; based on theoretical pore size Select the appropriate size limiting filter and use a pore size measuring instrument to check the actual pore size of the filter to ensure that the actual pore size deviation is ≤±5%; if the actual pore size deviation exceeds the range, the filter needs to be replaced or the pore size needs to be corrected. S23: Filtration efficiency verification; Take 100g of simulated granular material containing a known proportion of oversized particles, filter it using a calibrated filter, collect the filtered particles and test the residual amount of oversized particles, and ensure that the oversized particle removal efficiency is ≥99.8%; If the efficiency does not meet the standard, repeat steps S11-S12.

[0009] Preferably, the surface cleaning and purification in step 2 includes a process for cleaning and drying synthesized nanoparticles and a process for purifying nanoscale graphite particles. The specific parameters and processes are as follows: Cleaning and drying process for synthesized nanoparticles: S31: Pretreatment; Place the qualified synthetic nanoparticles in a sealed container, add deionized water, with a solid-liquid mass ratio of 1:5-1:8, and stir for 10-15 minutes for initial wetting; S32: Water jet homogenization and cleaning; The mixed system of the impregnated synthetic nanoparticles and water is fed into a water jet homogenizer for surface cleaning and dispersion treatment. After treatment, centrifugation is used to separate the particles from the cleaning water at a speed of 3000-5000 r / min for 10-15 min. S33: Drying treatment; The separated synthetic nanoparticles are placed in a vacuum drying oven and dried at a temperature of 120-180℃ and a vacuum degree of -0.08~-0.09MPa. During the drying process, samples are taken every 30 minutes to detect the moisture content of the particles until the moisture content is ≤0.3%, at which point the drying is stopped. Nanoscale graphite particle purification process: S41: Heating treatment; Place the qualified nano-scale graphite particles in a high-temperature furnace and heat them to 800-1200℃ at a heating rate of 5-10℃ / min. S42: Heat preservation and purification; heat preservation at the target temperature for 2-4 hours to remove impurities (such as ash and volatile organic compounds) from graphite particles. S43: Cooling and Purity Testing; After the heat preservation period, cool to room temperature at a rate of 3-5℃ / min, and take samples to test the purity of the purified graphite particles. Purity is calculated using the following formula: ; in, The initial purity (mass fraction, %) of nanoscale graphite particles before purification. To improve the purification and removal rate; requirements are as follows: ≥35% and ≥99.5%. If not, repeat steps S41-S42.

[0010] Preferably, the process parameter control for the water jet homogenization surface cleaning treatment in step 2 includes the following steps: S51: Jet pressure and flow rate calibration; determine the jet pressure based on the material of the synthesized nanoparticles (e.g., metal oxides or carbon-based). The initial value, ranging from 0.8 to 3 MPa, is used to calculate the theoretical jet velocity using the following formula. : ; in, The jet adaptation coefficient has a value range of [value range missing]. The actual jet velocity is measured using a flow velocity meter. If the deviation between the actual velocity and the theoretical velocity is greater than ±5%, the jet pressure is adjusted until the deviation meets the requirements. S52: Determination of cleaning time; Measurement of specific surface area of ​​synthesized nanoparticles. The unit is m 2 / g, calculate the required cleaning time using the following formula. : ; Require If calculated Then according to implement; S53: Cleaning effect verification; After cleaning, take a small amount of synthetic nanoparticles and use an X-ray fluorescence spectrometer to detect the surface impurity content (such as metal ions and non-metal impurities). The impurity content reduction rate is required to be ≥90%; If it does not meet the standard, extend the cleaning time or increase the jet pressure and clean again.

[0011] Preferably, the process for determining the component ratio and mixing of the composite powder in step 3 is as follows: S61: Component weighing; Based on 100 parts by mass of composite powder, weigh each component according to the following mass ratios: Synthetic nanoparticles: 60-75 parts by weight; Nanoscale graphite particles: 10-15 parts by weight; Nano-sized chrysotile asbestos particles: 3-5 parts by weight; Nano-sized white stone particles: 3-5 parts by weight; Weighing accuracy is controlled within ±0.1 parts by mass; S62: Premixing; The weighed nano-sized chrysotile asbestos particles and nano-sized white stone particles are first added to the mixer and stirred at a speed of 200-300 r / min for 10-15 min to achieve preliminary mixing; S63: Overall Mixing; Add the synthesized nanoparticles and nanoscale graphite particles to the premixed material, and continue stirring at 250-350 r / min for 20-30 min. During the stirring process, take samples every 5 min to check the mixing uniformity (use a laser particle size analyzer to check the particle distribution uniformity) to ensure that the mass ratio of each component is in accordance with the requirements. ,in, The mass percentage of synthesized nanoparticles. The percentage of nanoscale graphite particles by mass. The mass percentage of nano-sized chrysotile asbestos particles. The mass percentage of nano-sized white stone particles is determined by mixing them evenly to obtain a composite powder.

[0012] Preferably, the ultrasonic surface suspension energy treatment in step 3 includes the following specific process: S71: Powder pretreatment; Place the prepared composite powder in an ultrasonic treatment container, add a small amount of lubricant, the mass ratio of powder to lubricant is 10:1-8:1, stir for 5-10 minutes to initially moisten the powder and avoid powder flying during ultrasonication. S72: Intermittent ultrasound and stirring; Insert the ultrasound probe into the moistened composite powder, set the ultrasound equipment parameters: rated power 500-1500W, ultrasound frequency 25-60kHz, adopt intermittent ultrasound mode, ultrasound for 30 seconds, pause for 10 seconds, cycle; at the same time, start the stirring device to stir the powder at a rate of 50-100r / min. S73: Energy density monitoring and adjustment; During ultrasound treatment, the ultrasound energy density E is calculated in real time according to the following formula: ; in, Rated power of the ultrasonic equipment (unit: W). Total ultrasound processing time (unit: min). The volume of the composite powder (unit: L, calculated from the powder mass and bulk density); ensure The value range is 1800-3000 W·min / L; if If the signal is out of range, adjust the ultrasonic power or processing time. S74: Ultrasonic effect test; After ultrasonic treatment, take a small amount of composite powder and observe the particle dispersion state using a transmission electron microscope. The particle agglomerate size should be ≤200nm. If the agglomerate size exceeds the standard, extend the ultrasonic time or increase the ultrasonic power and reprocess.

[0013] Preferably, the blending and finished product preparation in step 4 includes the following specific processes and parameters: S81: First stage blending; the ultrasonically treated composite powder... With the first part of the lubricant Add to the mixing tank, where Calculate using the following formula: ; The first blending ratio coefficient is set to a value ranging from 1.3 to 2.0; the blending tank temperature is set to 50-60℃, the stirring speed to 200-300 r / min, and the stirring time to be specified. ; S82: Dilution and blending; Calculation of the mass of the second part of the lubricant. : ; in, The bulk density of the composite powder is expressed in g / cm³. 3 The value ranges from 1.2 to 1.8 g / cm³. 3 ; This refers to the density of the lubricant, expressed in g / cm³. 3 The value ranges from 0.85 to 0.95 g / cm³. 3 ;Will Add the corresponding lubricant to the mixing tank, maintain the temperature at 50-60℃, stir at 150-200 rpm, and stir for [duration missing]. Simultaneously verify Ensure that the dispersion concentration of the composite powder in the lubricant is 15-25% by mass; S83: Addition and mixing of auxiliary materials; Add the auxiliary materials to the mixing tank at a ratio of 1-2 parts by weight per 100 parts by weight of finished lubricant, maintain the temperature at 50-60℃, stir at a speed of 150-200 r / min, and stir for a period of time... And satisfy ; S84: Temperature control and uniformity detection; stop heating and allow the mixing system in the blending tank to cool naturally. Check the system temperature every 10 minutes. Once the temperature drops below 30℃, take a sample to test the uniformity U of the mixing system. The uniformity is calculated using the following formula: ; in, The standard deviation of particle size (in nm) of the aggregates in the blended system. The standard deviation of particle size (in nm) of the aggregates in the composite powder before blending is required. ≥94%; if not, stir again for 5-10 minutes and test again. S85: Finished product packaging; The uniformity of the mixed system is packaged using quantitative packaging equipment, with a packaging error of ≤±2% per bottle. After packaging, the bottles are sealed and labeled with product information.

[0014] Preferably, the excipients in step 4 consist of defoamers and antioxidants, and the preparation and addition of the excipients include the following steps: S91: Determination and weighing of auxiliary materials; Based on 100 parts by weight of finished lubricant, the total mass of auxiliary materials is 1-2 parts by weight, of which the mass ratio of defoamer to antioxidant is 1:1-1.5:1; the defoamer is selected from polyether-type defoamers (such as polyoxyethylene polyoxypropylene glycerol ether), and the antioxidant is selected from hindered phenolic antioxidants (such as 2,6-di-tert-butyl-p-cresol); the defoamer and antioxidant are accurately weighed according to the ratio, with a weighing accuracy of ±0.01g; S92: Premixing of excipients; add the weighed defoamer and antioxidant to a small mixer and stir for 5-8 minutes at a speed of 500-800 r / min and a temperature of 40-50℃ to obtain a uniform excipient premix. S93: Timing of addition; After step S92, check the amount of foam in the mixing system in the mixing tank: If the foam height is ≤5mm, add the auxiliary premix directly; If the foam height is >5mm, let it stand for 5-10 minutes until the foam dissipates before adding the auxiliary premix. S94: Verification of excipient dispersion; After the excipients are added and stirred, take a sample to observe the foam state of the mixture. The foam should be completely dissipated. If there is still foam, add 0.1-0.2 parts by weight of defoamer and continue stirring for 3-5 minutes.

[0015] Preferably, the synthesized nanoparticles in step 1 are metal oxide nanoparticles or carbon-based nanoparticles, and the particle selection and applicability verification includes the following process: Particle selection: Choose the particle type based on the friction conditions of the target machinery (e.g., high temperature, heavy load, corrosive environment). If the operating temperature is >200℃ or there is a corrosive medium, select metal oxide nanoparticles, specifically Al2O3, TiO2, or ZnO nanoparticles. If the operating conditions are normal temperature and medium to light load, carbon-based nanoparticles should be selected, preferably graphene or carbon nanotubes.

[0016] This invention provides a method for preparing composite materials rich in nanoparticles, which has the following beneficial effects: 1. Achieving a revolutionary transformation in friction patterns and significantly reducing friction loss: This invention ensures that composite powder particles can be precisely implanted into the tiny gaps of the working surface through strict particle size distribution screening and adaptability design, forming a bearing-like structure at the friction interface. This transforms traditional sliding friction into rolling friction, fundamentally reducing the coefficient of friction and wear, effectively reducing energy consumption, helping to improve energy utilization, and meeting the needs of green and low-carbon development.

[0017] 2. Excellent particle compatibility and dispersibility, resulting in stable and long-lasting lubrication: By employing scientific particle size control standards and diameter-limiting filtration technology, combined with ultrasonic surface suspension energy treatment and staged blending processes, the nanoparticles are ensured to be uniformly dispersed in the lubricant without significant agglomeration, and the particle size is precisely matched to the friction interface gap, avoiding lubrication failure caused by oversized or unevenly dispersed particles. At the same time, through water jet homogenization cleaning and high-temperature purification processes, impurities and ash on the particle surface are effectively removed, further improving the stability of the lubrication interface and extending the continuous lubrication cycle.

[0018] 3. Synergistic effect of composite components, outstanding anti-wear and friction reduction performance: The composite powder adopts a scientific ratio of synthetic nanoparticles, nano-scale graphite particles, chrysotile asbestos particles and white stone particles, and the functions of each component are complementary; graphite particles provide excellent lubricity, metal oxide / carbon-based nanoparticles enhance wear resistance, and chrysotile asbestos and white stone particles improve interfacial support, synergistically achieving the integrated functions of lubrication, anti-wear and support. Compared with single-component nano lubricants, the anti-wear performance is greatly improved, which can significantly extend the service life of mechanical parts.

[0019] 4. Wide range of applications and adaptability to complex working conditions: The particle type can be flexibly selected according to the friction conditions (temperature, load, medium environment) of the target machine; suitable metal oxide nanoparticles are selected for high temperature or corrosive working conditions, and suitable carbon-based nanoparticles are selected for medium and light load working conditions at room temperature. At the same time, the stability of the product in different environments can be improved by precise proportioning and addition of auxiliary materials. It can be widely used in industrial machinery, transportation, precision equipment and other fields, solving the problem of limited application scenarios of existing technologies.

[0020] 5. High safety and no impact on original equipment performance: This invention avoids excessive particle accumulation or size exceeding limits by precisely controlling particle size and dispersion concentration. It does not require changing the key dimensional data of core components and will not negatively affect the equipment assembly accuracy and operational safety. At the same time, the vacuum drying and high-temperature purification process ensures that the product is free of harmful impurities and there is no additional pollution during use, thus ensuring the safety of the equipment and the environment.

[0021] 6. The preparation process is highly controllable and the product quality is stable: The entire preparation process is subject to full-process quality control through multiple detection and verification mechanisms. Each process parameter (such as ultrasonic energy density, mixing temperature, and stirring speed) has clear quantitative standards, which can realize large-scale production. Moreover, the product packaging error is small and the quality consistency is high, meeting the needs of industrial-scale application. Attached Figure Description

[0022] Figure 1 This is a uniform distribution diagram of C and Si elements in Embodiment 1 of the present invention; Figure 2 This is a close distribution diagram of Al and C elements in Embodiment 2 of the present invention; Figure 3 This is a diagram illustrating the antioxidant properties of Embodiment 2 of the present invention. Detailed Implementation

[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] This invention provides a technical solution: a method for preparing a composite material rich in nanoparticles, using a lubricant as a carrier, dispersing a composite powder containing synthetic nanoparticles, nano-scale graphite particles, nano-scale chrysotile asbestos particles and nano-scale white stone particles in the lubricant, the resulting lubricant can be embedded in the tiny gaps between two or more working surfaces that slide and rub against each other and produce a bearing-like effect, realizing the transformation of sliding friction into rolling friction.

[0025] As Figure 1 shown, Example 1, normal temperature medium-light load working condition (suitable for general mechanical transmission systems): Working condition parameters and raw material selection: working temperature 25-80°C, load ≤500N, no corrosive medium, micro-gap of friction interface 80-150nm; Raw material selection: Synthetic nanoparticles: carbon-based nanoparticles (graphene), initial particle size range 10-100nm; Nano-scale graphite particles: initial purity 96.2%, particle size range 15-110nm; Nano-scale chrysotile particles: particle size range 20-90nm; Nano-scale dolomite particles: particle size range 18-85nm; Lubricant carrier: mineral-based lubricating oil (density oil = 0.90g / cm 3 ); Auxiliary materials: polyoxyethylene polyoxypropylene glyceryl ether (defoamer), 2,6-di-tert-butyl-p-cresol (antioxidant).

[0026] The preparation steps are as follows: Step 1, particle size gradation screening: Sample collection and detection: 3 parallel samples are respectively drawn from four types of particles, each sample has a mass of 8g, and the particle size distribution is measured by a Malvern 3000 laser particle size analyzer. The results are as follows: ; Span coefficient calculation and conformity judgment: according to the formula to calculate the span coefficient: Graphene: Sample 1 (unqualified), needs to be re-screened; after multiple grading screenings, the final qualified graphene samples are: Sample 1 (50 / 79 / 105), Sample 2 (51 / 80 / 106), Sample 3 (49 / 78 / 104), are respectively , , (all ≤0.7), and are in the range of 20-80nm, ≤120nm, judged as qualified; Nano-scale graphite: qualified samples after screening: Sample 1 (55 / 75 / 105), Sample 2 (56 / 76 / 106), Sample 3 (54 / 74 / 104), are respectively , , (all ≤0.7), and is between 20 and 80 nm, ≤ 120 nm, it is determined as qualified; Nano-scale chrysotile and white stone particles: 3 samples all are ≤ 0.65, 35-60 nm, ≤ 100 nm, it is directly determined as qualified.

[0027] Setting of restricted-diameter filter: Pore size calculation: take various particles the maximum value is 106 nm (nano-scale graphite), the safety filtration factor α = 0.15, according to the formula calculation, ; Model selection and calibration: select a restricted-diameter filter with 120 nm specification, the actual pore size detected by a pore size measuring instrument is 122.5 nm, the deviation is ≤ ±5%, which is qualified after calibration; Filtration efficiency verification: take 100 g of simulated graphite particle material containing 5% over-limit particles (particle size > 120 nm), adjust the filter pore size to 118 nm and then perform filtration, the residual amount of over-limit particles detected is 0.01 g, the removal efficiency meets the requirements.

[0028] Removal of over-limit particles and re-inspection: batch screening is performed on four types of particles by using the calibrated restricted-diameter filter, after removing over-limit particles, 3 samples are randomly selected for re-inspection, the re-inspection qualification rate is 99.7%, the particles can be implanted into gaps of 80-150 nm, and the screening is completed.

[0029] Step 2: Surface cleaning and purification: Cleaning and drying of synthetic nanoparticles (graphene): Pretreatment: take 500 g of qualified screened graphene, place it in a sealed container, add 3000 g of deionized water (solid-liquid mass ratio 1:6), stir for 12 min for preliminary wetting; Hydrometric jet homogenization cleaning: feed the mixed system into hydrometric jet homogenization equipment, graphene is a carbon-based material, the initial jet pressure is 1.5 MPa, according to the formula (k=1.0 m / (s·MPa 0 · 5 )) for calculating the theoretical flow rate , the actually detected flow rate is 1.20 m / s, the deviation is 1.6% ≤ ±5%; measure the specific surface area of graphene , according to the formula calculate the cleaning time ≥ 5 min, execute at 7.8 min; After cleaning, centrifugation was performed at 4000 r / min for 12 min to separate particles from cleaning water. The surface impurity content was detected using X-ray fluorescence spectrometry. The impurity reduction rate was 92.5% ≥ 90%, indicating that the cleaning was qualified. Drying process: Place the graphene in a vacuum drying oven at 150℃ and -0.085MPa. Take a sample every 30 minutes to test the moisture content. After 6 hours, if the moisture content is ≤0.3% (0.25%), stop drying.

[0030] Purification of nanoscale graphite particles: Heating treatment: Take 200g of qualified graphite particles, place them in a high-temperature furnace, and heat them to 1000℃ at a rate of 8℃ / min; Heat preservation and purification: Heat preservation at 1000℃ for 3 hours to remove ash and volatile organic compounds; Cooling and purity testing: Cool to room temperature at a rate of 4℃ / min, according to the formula... Calculate purity, initial purity If the purification and removal rate η = 38.5%, then ≥99.5%, purified to standard.

[0031] Step 3: Preparation and ultrasonic treatment of composite powder: Composite powder component ratio and mixing: Component weighing: Based on 100 parts by mass of composite powder, weigh each component as follows: 70 parts by mass of graphene, 12 parts by mass of nano-graphite, 4 parts by mass of nano-chrysotile asbestos, and 4 parts by mass of nano-white stone, with a weighing accuracy of ±0.05 parts by mass. Premixing: Add chrysotile asbestos and white stone granules to the mixer and stir at 250 r / min for 12 min to achieve preliminary mixing; Overall mixing: Add graphene and graphite particles, stir at 300 r / min for 25 min, take samples every 5 min to check the mixing uniformity, and finally the total mass ratio of each component is 100%, the mixing uniformity is qualified, and 100 kg of composite powder is obtained.

[0032] Ultrasonic surface suspension energy treatment: Powder pretreatment: Place 100 kg of composite powder in an ultrasonic treatment container, add 12.5 kg of lubricant (powder to lubricant mass ratio 8:1), and stir for 8 minutes to initially moisten; Intermittent ultrasound and stirring: The ultrasound equipment has a rated power of 1000W and an ultrasound frequency of 40kHz. It adopts a cycle mode of 30 seconds of ultrasound followed by a 10-second pause. At the same time, the powder is stirred at a rate of 80r / min. Energy density monitoring: Bulk density of composite powder ,volume According to the formula Controlling energy density, setting the total ultrasound time ,but It falls within the range of 1800-3000 W·min / L; Ultrasonic effect test: After ultrasonic treatment, the particle agglomerates were observed with a transmission electron microscope. The particle size was ≤180nm≤200nm, indicating that the treatment was qualified.

[0033] Step 4, Blending and Finished Product Preparation: First stage of blending: 100 kg of ultrasonically treated composite powder is mixed with the first part of the lubricant. Add to the mixing tank, first mixing ratio coefficient According to the formula calculate The mixing tank temperature was 55℃, the stirring speed was 250r / min, and the stirring time was 90min.

[0034] Dilution and blending: According to the patent requirements, "the dispersion concentration of the composite powder in the lubricant is 15-25% by mass" and " "If the dispersion concentration is set at 20% (mass%), then the total mass of the finished lubricant product..." The total mass of lubricant is Therefore, the second part is about the quality of the lubricant. ,satisfy ; Add 240 kg of lubricant, maintain the temperature at 55°C, stir at 180 r / min, and stir for 15 min.

[0035] Addition and mixing of auxiliary materials: The total mass of the finished lubricant is 500 kg, and the total mass of the auxiliary materials is calculated as 1.5 parts by mass (i.e. 7.5 kg). The mass ratio of defoamer to antioxidant is 1.2:1. Weigh 4.1 kg of defoamer and 3.4 kg of antioxidant (accuracy ±0.01 g). Additives premixing: Add to a small mixer, stir at 600 r / min and 45℃ for 6 min to obtain a premix; If the foam height in the mixing tank is ≤3mm, add the premixed auxiliary materials directly, maintain the temperature at 55℃, stir at 180r / min, and stir for 15min to meet the requirements. ; After stirring, observe that the foam has completely dissipated and the auxiliary materials are properly dispersed.

[0036] Temperature control and uniformity testing: Stop heating and allow natural cooling. After 2 hours, the system temperature drops to 28℃. Then, use the formula... Uniformity was measured by the standard deviation of the aggregate size before blending. After mixing ,but ≥94%, uniformity is acceptable.

[0037] Finished product packaging: Quantitative packaging equipment is used, with each bottle containing 1kg. The packaging error is ±1.5% ≤ ±2%. Product information is labeled after sealing.

[0038] like Figure 2 As shown, Example 2: High-temperature corrosion conditions (suitable for transmission components of chemical equipment). Operating parameters and material selection: operating temperature 220-300℃, load ≤800N, presence of slightly corrosive media (acidic vapor), and minute gaps at the friction interface of 50-100nm; Raw material selection: Synthesized nanoparticles: metal oxide nanoparticles (Al2O3), with an initial particle size range of 15-90 nm; Nanoscale graphite particles: initial purity 95.8%, particle size range 20-100nm; Nanoscale chrysotile asbestos particles: particle size range 18-85nm; Nanoscale white stone particles: particle size range 20-88nm; Lubricant carrier: Synthetic ester lubricating oil (density ρoil = 0.92 g / cm³) 3 ); Excipients: Polyoxyethylene polyoxypropylene glycerol ether (defoamer), 2,6-di-tert-butyl-p-cresol (antioxidant).

[0039] Differentiated implementation of key steps: Particle size distribution screening: After screening, 3 samples of Al2O3 nanoparticles were selected. The corresponding nm wavelengths are 30 / 55 / 95nm, 31 / 56 / 98nm, and 29 / 54 / 93nm, respectively, with a span coefficient S ≤ 0.65 for all three. ≤120nm, qualified; theoretical pore size of the limiting filter After calibration, the actual pore size is 112.5 nm, and the filtration efficiency is 99.9%.

[0040] Surface cleaning and purification: Al2O3 is a metal oxide. The initial pressure of the homogeneous and clean water jet is 2.5 MPa, and the theoretical flow rate is... The actual flow velocity was 1.55 m / s, with a deviation of 1.9%; the specific surface area... Cleaning time The cleaning process, which lasts for 5 minutes, resulted in a 93.2% reduction in impurities after cleaning. Graphite particle purification: heating rate 7℃ / min, target temperature 1100℃, holding time 3.5h, purification removal rate η=40.2%, purity .

[0041] Composite powder ratio: 72 parts by weight of Al2O3, 13 parts by weight of nano-graphite, 3.5 parts by weight of chrysotile asbestos, and 3.5 parts by weight of white stone. Total mixing speed: 320 r / min. Stirring time: 28 min.

[0042] Ultrasonic processing: ultrasonic power 1200W, frequency 50kHz, energy density After ultrasound, the particle size of the aggregates is ≤190nm.

[0043] Blending process: First blending ratio coefficient , ;If the dispersion concentration of the composite powder is set to 22% (mass%), then the total mass of the finished lubricant product is... The total mass of lubricant is Therefore ,satisfy The total mass of the auxiliary materials is calculated as 1.8 parts by weight, and the ratio of defoamer to antioxidant is 1.5:1.

[0044] The effectiveness of the example is verified as follows: Effect Verification 1: Friction and Wear Performance Test. This test verifies whether the lubricant can transform sliding friction into rolling friction, fundamentally reducing the coefficient of friction and wear. The test plan is as follows: Test equipment: MMW-1 vertical universal friction and wear tester (compliant with GB / T39174-2020 "Determination of Friction and Wear Properties of Lubricants - Ball-Disc Method"). Test sample: Friction pair: 45# steel disc (diameter 30mm, surface roughness Ra=0.8μm), GCr15 steel ball (diameter 6mm, hardness HRC62-64). Lubricant dosage: 5 mL of the finished product from Examples 1 and 22, and the control group was the same type of conventional lubricant (without nanoparticles). Test conditions: Example 1 (light load at room temperature): load 300N, rotation speed 500r / min, temperature 50℃, test duration 2h; Example 2 (High-Temperature Corrosion): Load 600N, rotation speed 800r / min, temperature 250℃, 5% acidic steam (simulating chemical working conditions), test duration 3h; Test indicators: real-time recording of friction coefficient (average value taken every 10 minutes), wear of steel disc after test (using the "weight loss method": weighing the mass difference before and after wear with an electronic balance, with an accuracy of 0.1 mg), and wear trajectory morphology of steel disc (observed using a ZeissSigma 300 field emission scanning electron microscope (SEM).

[0045] Test Results and Explanation: ; The low coefficient of friction and low wear in Examples 1 and 2 confirm the effectiveness of the design of "precisely embedding composite powder into micro gaps to form a bearing-like structure". The stable performance of Example 2 in a high-temperature acidic environment verifies the synergistic advantages of the components "metal oxide nanoparticles (Al2O3) and high-temperature purified graphite", which solves the problem of performance degradation of traditional lubricants under complex working conditions.

[0046] 2. Performance Verification: Stability Test, verifying the stability of the lubricant during storage and long-term operation. Stability during room temperature storage (adapted to the general scenario of Example 1); Test conditions: After sealing, the finished product of Example 1 was stored in a constant temperature environment of 25°C for 12 months, and samples were taken for testing every 3 months; Test indicators: particle dispersion uniformity (using a laser particle size analyzer to measure the particle size distribution of agglomerates), lubricant appearance (whether it separates into layers or precipitates); Test results: After 12 months of storage, the average particle size of the agglomerates was ≤200nm (initially 180nm), and the uniformity remained at 93.5% (initially 94%). The appearance showed no stratification or sedimentation, and the flowability was consistent with the initial state.

[0047] Stability under high-temperature conditions (adapted to chemical industry scenario in Example 2); Test conditions: The finished product of Example 2 was continuously circulated in a constant temperature furnace at 250℃ for 500 hours (simulating the continuous working mode of chemical equipment), and samples were taken for testing every 100 hours; Test indicators: Antioxidant performance (oxidation induction period was measured using GB / T12581-2021 "Determination of Oxidation Characteristics of Mineral Oil with Inhibitors"), corrosion resistance performance (copper strip corrosion test, GB / T5096-2017, rating). like Figure 3 As shown, the test results are as follows: the oxidation induction period lasts for more than 120 minutes (initially 125 minutes), with no obvious oxidation and deterioration; the copper sheet corrosion rating is 1a (no corrosion traces), which is far superior to the 2b rating of traditional lubricants.

[0048] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a composite material rich in nanoparticles, characterized in that, Using a lubricant as a carrier, a composite powder containing synthetic nanoparticles, nano-sized graphite particles, nano-sized chrysotile asbestos particles, and nano-sized white stone particles is dispersed in the lubricant. The resulting lubricant can be embedded in the tiny gaps between two or more mutually sliding and rubbing working surfaces and generate a bearing-like effect, realizing the transformation of sliding friction into rolling friction. The process includes the following steps: Step 1, Particle size distribution screening: Based on the friction application scenario of the target machinery, synthetic nanoparticles, nano-scale graphite particles, nano-scale chrysotile asbestos particles and nano-scale white stone particles are screened to remove particles with excessive particle size and ensure that the particles are suitable for the tiny gaps on the working surface. Step 2, Surface cleaning and purification: The screened synthetic nanoparticles are surface cleaned and dispersed and then dried. The screened nanoscale graphite particles are then purified at high temperature. Step 3, Composite Powder Preparation and Ultrasonic Treatment: The synthetic nanoparticles and nano-scale graphite particles after surface cleaning and purification are mixed with the screened nano-scale chrysotile asbestos particles and nano-scale white stone particles in a preset mass ratio to obtain composite powder. The composite powder is then subjected to ultrasonic surface suspension energy treatment. Step 4, Blending and Finished Product Preparation: The ultrasonically treated composite powder and lubricant are blended and stirred in stages. After adding auxiliary materials, stirring is continued. After the temperature of the mixed system drops to the preset temperature, it is packaged to obtain a lubricant rich in nanoparticles.

2. The method for preparing a nanoparticle-rich composite material according to claim 1, characterized in that, The particle size distribution screening described in step 1 is based on the particle size distribution span coefficient. The core criterion is particle size distribution screening, and the specific operational procedures include the following: S11: Particle Sample Collection and Particle Size Distribution Detection; At least three parallel samples were drawn from each of the synthetic nanoparticles, nano-scale graphite particles, nano-scale chrysotile asbestos particles, and nano-scale white stone particles to be screened. Each sample weighed 5-10g. The particle size distribution data of each sample was determined using a laser particle size analyzer. , , value; S12: Span coefficient calculation and compliance determination; based on each sample , , The span coefficient is calculated using the following formula. : ; in, The particle size value when the cumulative particle size distribution reaches 10%, in nm; The median particle size when the cumulative particle size distribution reaches 50%, in nm; This refers to the particle size value when the cumulative particle size distribution reaches 90%, in nm; if the span coefficient S of three parallel samples of a certain type of particle is ≤0.7, and All are in the 20-80nm range. If all particles are ≤120nm, the particle size is considered acceptable; otherwise, they need to be screened again. S13: Removal and re-inspection of out-of-limit particles; For qualified particles, use a diameter-limiting filter for batch screening to remove out-of-limit particles; After screening, randomly select 3 parallel samples of the screened particles and repeat steps S21-S12 for re-inspection to ensure that the re-inspection pass rate is ≥99.5% and that the particles can be implanted into the micro gaps of the working surface of 50-200nm.

3. The method for preparing a nanoparticle-rich composite material according to claim 2, characterized in that, Step 1 uses a diameter-limiting filter to remove particles that exceed the size limit, and the filter pore size setting includes the following process: S21: Pore size calculation; calculate the pore size of qualified particles. The maximum value is calculated using the following formula to determine the theoretical pore size of the filter. : ; in, The safety filtering coefficient has a value range of 0.12-0.

18. S22: Filter selection and pore size calibration; based on theoretical pore size Select the appropriate size limiting filter and use a pore size measuring instrument to check the actual pore size of the filter to ensure that the actual pore size deviation is ≤±5%; if the actual pore size deviation exceeds the range, the filter needs to be replaced or the pore size needs to be corrected. S23: Filtration efficiency verification; Take 100g of simulated granular material containing a known proportion of oversized particles, filter it using a calibrated filter, collect the filtered particles and test the residual amount of oversized particles, and ensure that the oversized particle removal efficiency is ≥99.8%; If the efficiency does not meet the standard, repeat steps S11-S12.

4. The method for preparing a nanoparticle-rich composite material according to claim 3, characterized in that, Step 2, surface cleaning and purification, includes a process for cleaning and drying synthesized nanoparticles and a process for purifying nanoscale graphite particles. The specific parameters and processes are as follows: Cleaning and drying process for synthesized nanoparticles: S31: Pretreatment; Place the qualified synthetic nanoparticles in a sealed container, add deionized water, with a solid-liquid mass ratio of 1:5-1:8, and stir for 10-15 minutes for initial wetting; S32: Water jet homogenization and cleaning; The mixed system of the impregnated synthetic nanoparticles and water is fed into a water jet homogenizer for surface cleaning and dispersion treatment. After treatment, centrifugation is used to separate the particles from the cleaning water at a speed of 3000-5000 r / min for 10-15 min. S33: Drying treatment; The separated synthetic nanoparticles are placed in a vacuum drying oven and dried at a temperature of 120-180℃ and a vacuum degree of -0.08~-0.09MPa. During the drying process, samples are taken every 30 minutes to detect the moisture content of the particles until the moisture content is ≤0.3%, at which point the drying is stopped. Nanoscale graphite particle purification process: S41: Heating treatment; Place the qualified nano-scale graphite particles in a high-temperature furnace and heat them to 800-1200℃ at a heating rate of 5-10℃ / min. S42: Heat preservation and purification; heat preservation at the target temperature for 2-4 hours to remove impurities from graphite particles; S43: Cooling and Purity Testing; After the heat preservation period, cool to room temperature at a rate of 3-5℃ / min, and take samples to test the purity of the purified graphite particles. Purity is calculated using the following formula: ; in, To improve the initial purity of the nanoscale graphite particles before purification, To improve the purification and removal rate; requirements are as follows: ≥35% and ≥99.5%. If not, repeat steps S41-S42.

5. The method for preparing a nanoparticle-rich composite material according to claim 4, characterized in that, The process parameter control for the water jet homogenization surface cleaning treatment in step 2 includes the following steps: S51: Jet pressure and flow rate calibration; determine the jet pressure based on the material of the synthesized nanoparticles. The initial value, ranging from 0.8 to 3 MPa, is used to calculate the theoretical jet velocity using the following formula. : ; in, The jet adaptation coefficient has a value range of [value range missing]. The actual jet velocity is measured using a flow velocity meter. If the deviation between the actual velocity and the theoretical velocity is greater than ±5%, the jet pressure is adjusted until the deviation meets the requirements. S52: Determination of cleaning time; Measurement of specific surface area of ​​synthesized nanoparticles. The unit is m 2 / g, calculate the required cleaning time using the following formula. : ; Require If calculated Then according to implement; S53: Cleaning effect verification; After cleaning, take a small amount of synthetic nanoparticles and use an X-ray fluorescence spectrometer to detect the surface impurity content. The impurity content reduction rate should be ≥90%; If it does not meet the standard, extend the cleaning time or increase the jet pressure and clean again.

6. The method for preparing a nanoparticle-rich composite material according to claim 5, characterized in that, The process for determining the component ratio and mixing of the composite powder in step 3 is as follows: S61: Component weighing; Based on 100 parts by mass of composite powder, weigh each component according to the following mass ratios: Synthetic nanoparticles: 60-75 parts by weight; Nanoscale graphite particles: 10-15 parts by weight; Nano-sized chrysotile asbestos particles: 3-5 parts by weight; Nano-sized white stone particles: 3-5 parts by weight; Weighing accuracy is controlled within ±0.1 parts by mass; S62: Premixing; The weighed nano-sized chrysotile asbestos particles and nano-sized white stone particles are first added to the mixer and stirred at a speed of 200-300 r / min for 10-15 min to achieve preliminary mixing; S63: Overall Mixing; Add the synthesized nanoparticles and nanoscale graphite particles to the premixed material, and continue stirring at 250-350 r / min for 20-30 min. During the stirring process, take samples every 5 min to check the mixing uniformity and ensure that the mass ratio of each component is in accordance with the requirements. ,in, The mass percentage of synthesized nanoparticles. The percentage of nanoscale graphite particles by mass. The mass percentage of nano-sized chrysotile asbestos particles. The mass percentage of nano-sized white stone particles is determined by mixing them evenly to obtain a composite powder.

7. The method for preparing a nanoparticle-rich composite material according to claim 6, characterized in that, The ultrasonic surface suspension energy treatment described in step 3 includes the following specific process: S71: Powder pretreatment; Place the prepared composite powder in an ultrasonic treatment container, add a small amount of lubricant, the mass ratio of powder to lubricant is 10:1-8:1, stir for 5-10 minutes to initially moisten the powder and avoid powder flying during ultrasonication. S72: Intermittent ultrasound and stirring; Insert the ultrasound probe into the moistened composite powder, set the ultrasound equipment parameters: rated power 500-1500W, ultrasound frequency 25-60kHz, adopt intermittent ultrasound mode, ultrasound for 30 seconds, pause for 10 seconds, cycle; at the same time, start the stirring device to stir the powder at a rate of 50-100r / min. S73: Energy density monitoring and adjustment; During ultrasound treatment, the ultrasound energy density E is calculated in real time according to the following formula: ; in, The rated power of the ultrasonic equipment. This represents the total ultrasound processing time. For the volume of the composite powder; ensure The value range is 1800-3000 W·min / L; if If the signal is out of range, adjust the ultrasonic power or processing time. S74: Ultrasonic effect test; After ultrasonic treatment, take a small amount of composite powder and observe the particle dispersion state using a transmission electron microscope. The particle agglomerate size should be ≤200nm. If the agglomerate size exceeds the standard, extend the ultrasonic time or increase the ultrasonic power and reprocess.

8. The method for preparing a nanoparticle-rich composite material according to claim 7, characterized in that, Step 4, the blending and finished product preparation, includes the following specific processes and parameters: S81: First stage blending; the ultrasonically treated composite powder... With the first part of the lubricant Add to the mixing tank, where Calculate using the following formula: ; The first blending ratio coefficient is set to a value ranging from 1.3 to 2.0; the blending tank temperature is set to 50-60℃, the stirring speed to 200-300 r / min, and the stirring time to be specified. ; S82: Dilution and blending; Calculate the mass of the lubricant in Part Two : ; in, The bulk density of the composite powder is expressed in g / cm³. 3 The value ranges from 1.2 to 1.8 g / cm³. 3 ; This refers to the density of the lubricant, expressed in g / cm³. 3 The value ranges from 0.85 to 0.95 g / cm³. 3 ;Will Add the corresponding lubricant to the mixing tank, maintain the temperature at 50-60℃, stir at 150-200 rpm, and stir for [duration missing]. Simultaneously verify Ensure that the dispersion concentration of the composite powder in the lubricant is 15-25% by mass; S83: Addition and mixing of auxiliary materials; Add the auxiliary materials to the mixing tank at a ratio of 1-2 parts by weight per 100 parts by weight of finished lubricant, maintain the temperature at 50-60℃, stir at a speed of 150-200 r / min, and stir for a period of time... And satisfy ; S84: Temperature control and uniformity detection; stop heating and allow the mixing system in the blending tank to cool naturally. Check the system temperature every 10 minutes. Once the temperature drops below 30℃, take a sample to test the uniformity U of the mixing system. The uniformity is calculated using the following formula: ; in, This represents the standard deviation of particle size agglomerates in the blended system. The standard deviation of particle size agglomerates in the composite powder before blending is required. ≥94%; if not, stir again for 5-10 minutes and test again. S85: Finished product packaging; The uniformity of the mixed system is packaged using quantitative packaging equipment, with a packaging error of ≤±2% per bottle. After packaging, the bottles are sealed and labeled with product information.

9. The method for preparing a nanoparticle-rich composite material according to claim 8, characterized in that, The excipients mentioned in step 4 consist of defoamers and antioxidants. The preparation and addition of the excipients include the following process: S91: Determination and weighing of auxiliary materials; Based on 100 parts by weight of finished lubricant, the total mass of auxiliary materials is 1-2 parts by weight, of which the mass ratio of defoamer to antioxidant is 1:1-1.5:1; the defoamer is selected from polyether-type defoamers, and the antioxidant is selected from hindered phenolic antioxidants; the defoamer and antioxidant are weighed accurately according to the ratio, with a weighing accuracy of ±0.01g; S92: Premixing of excipients; add the weighed defoamer and antioxidant to a small mixer and stir for 5-8 minutes at a speed of 500-800 r / min and a temperature of 40-50℃ to obtain a uniform excipient premix. S93: Timing of addition; After step S92, check the amount of foam in the mixing system in the mixing tank: If the foam height is ≤5mm, add the auxiliary premix directly; If the foam height is >5mm, let it stand for 5-10 minutes until the foam dissipates before adding the auxiliary premix. S94: Verification of excipient dispersion; After the excipients are added and stirred, take a sample to observe the foam state of the mixture. The foam should be completely dissipated. If there is still foam, add 0.1-0.2 parts by weight of defoamer and continue stirring for 3-5 minutes.

10. The method for preparing a nanoparticle-rich composite material according to claim 9, characterized in that, The synthesized nanoparticles in step 1 are metal oxide nanoparticles or carbon-based nanoparticles, and the particle selection and applicability verification include the following process: Particle selection; Select the particle type based on the friction conditions of the target machinery: If the operating temperature is >200℃ or there is a corrosive medium, select metal oxide nanoparticles, specifically Al2O3, TiO2, or ZnO nanoparticles. If the operating conditions are normal temperature and medium to light load, carbon-based nanoparticles should be selected, preferably graphene or carbon nanotubes.